Recent Progress in Electrocatalytic Glycerol Oxidation. Issue 2 (16th December 2020) - Fan, Linfeng; Liu, Bowen; Liu, Xi; Senthilkumar, Nangan; Wang, Genxiang; Wen, Zhenhai
Abstract : Glycerol, as the major by‐product of biodiesel, can be oxidized into diverse value‐added chemical products via either traditional chemical methods or electrochemical routes. Electrocatalytic glycerol oxidation reaction (GOR) driven by renewable‐derived electricity (e.g., wind and solar) is a promising pathway for fine chemicals production. In an electrochemical cell, GOR can be coupled with various cathodic reactions, including hydrogen evolution reaction (HER), CO2 reduction reaction (CO2 RR), and oxygen reduction reaction (ORR); in this manner, different benefits of either energy effectiveness or additional value‐added products can be obtained depending on the cathode reduction reaction selected. Comprehensively understanding of electrocatalytic GOR and the associated processes is of great significance to promote its industrial application. Herein, recent progress of GOR is focused on. The background of biomass‐derived glycerol valorization to energy and value‐added chemicals as well as the electrochemical conversion techniques via GOR is introduced. Then, the electrocatalytic reaction pathways, the potential application of GOR, and the measurement method for products are also discussed and summarized. Special emphasis is put on the design and the development of high‐selectivity and high‐activity electrocatalysts for GOR. Finally, the challenges and the future prospects in the fields of GOR are highlighted. Abstract : The present review focuses on summarizing the recent progress of electrolytic glycerol oxidation, aiming to provide an overview on fundamentals, reaction mechanisms, application in fuel cells and electrolyzers, and electrocatalysts development regarding the topic of glycerol oxidation reaction (GOR).